From Oratory to Debate: Parliamentarisation of Deliberative Rhetoric in Westminster - Palonen, Kari (Nomos Verlagsgesellschaft mbH & Co. KG, 2016)
Recent studies manifest a new interest in the politics of internal parliamentary practices. The book presents a thesis that a shift from oratory to debate characterises the parliamentarisation of deliberative rhetoric. Parliamentary speeches are intelligible only as political interventions pro et contra to debates on motions on the agenda and the agenda-setting itself.Scholars of rhetoric and parliaments have been slow to recognise this shift and its political implications. The book analyses the rhetoric of Westminster-related writings from late 18th century to WWII among scholars and others outsiders in contrast to parliamentary insiders (officials, journalists, members). A special attention is given to John Stuart Mill and Walter Bagehot as the most prominent British parliamentary theorists and to cases studies on actual parliamentary debates. With its procedures and ways of dealing time the Westminster-style parliament is an exemplary political assembly of debating pro et contra.